Determining the suitable settlement areas in Alanya with GIS-based site selection analyses - Dogan, Sedat; Kilicoglu, Cem; Akinci, Halil; Sevik, Hakan; Cetin, Mehmet (Springer Science and Business Media LLC, 2022)
Urbanization, which is defined as an irreversible global-scale problem nowadays, necessitates the foundation of new settlement areas. In general, no sufficient scientific assessment and analysis were performed during these processes, and thus, various natural disasters cost the loss of many lives and properties every year. Nevertheless, considering the areas that are risky in terms of natural disasters during the selection of settlement areas might prevent a large-scale loss of lives and properties because of natural disasters. Within the scope of this study, it was aimed to determine suitable settlement areas in the Alanya district, which is one of the significant points of interest for tourists in our country and has a large population and new settlement areas because of this increasing population. Within this scope, besides the risks of flood and landslide that are the most important natural disasters in the region, and a forest fire that is among the most significant risks for the region, also the biocomfort zones were included in the assessments. As a result of the study, it was determined that the most important natural disaster risk was flooding in a large portion of the region and that only 6.72% of the study area was suitable for settlement in terms of all the criteria examined in the present study.
Keywords: Disasters; Urbanization; Geographic Information Systems; Floods; Landslides; 13. Climate action; 11. Sustainability; 15. Life on land